REVIEW ARTICLE: NANOHERBAL AS A NATURAL SOLUTION FOR BACTERIAL DIARRHEA PROBLEMS - Embas Saraswati, Dewa Ayu; Jafar, Garnadi; Sulaeman, Agus; Mulyani, Yani (Medical Sains : Jurnal Ilmiah Kefarmasian, 2024)
Diarrhea is a global health problem that is often caused by bacterial infections, including Escherichia coli and Staphylococcus aureus. The use of conventional antibiotics in treating diarrhea often faces challenges, such as drug resistance and adverse side effects. As an alternative, current research interest is focused on the use of nanoparticles from herbal ingredients as potential antibacterial agents in the treatment of diarrhea. This review article aims to present the latest developments in the use of herbal nanoparticles as an anti-bacterial therapy for diarrhea. The literature search method was carried out via PubMed, Science Direct, and Google Scholar using relevant keywords. Selected articles must meet inclusion criteria, such as originality, language, period, and availability of full text. After the selection process, articles that meet the criteria will be reviewed to identify findings related to the use of herbal nanoparticles in treating diarrhea. Data analysis was conducted to compare the findings of each article and draw appropriate conclusions. Therefore, this review article aims to provide a comprehensive understanding of the potential use of nanoparticles from herbal ingredients as an effective and safe solution to treat diarrhea problems, while also highlighting interesting research possibilities to be carried out in the future. effectiveness and bioavailability in the treatment of diarrhea. By increasing absorption and penetration into bacterial cells, this therapy can serve as an effective and sustainable antibacterial agent ...